2020
DOI: 10.1002/jat.4053
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects induced by occupational exposure to refractory ceramic fibers

Abstract: Refractory ceramic fibers (RCFs) are increasingly used as heating‐insulated materials in various industries. However, toxicological and epidemiological studies focusing on the adverse effects of RCFs were still insufficient, particularly in China. We conducted a cross‐sectional study to evaluate comprehensively the associations between occupational exposure to RCFs and respiratory health effects among Chinese workers. We measured and calculated cumulative RCFexposure levels of RCFs workers from the biggest RCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“… 163 A study in Chinese workers reported adverse respiratory effects of RCF and altered lung damage and oxidative markers. 164 …”
Section: Discussionmentioning
confidence: 99%
“… 163 A study in Chinese workers reported adverse respiratory effects of RCF and altered lung damage and oxidative markers. 164 …”
Section: Discussionmentioning
confidence: 99%
“…ere is a negative correlation between TGF-β1 and CC16 levels, indicating that inhibiting TGF-β1 might enhance the activity of club cells (Gu et al 2021). Hydrogen sul de therapy has been shown to mitigate COPD induced by cigarette smoke through the inhibition of the TGF-β1/Smad pathway (Wang et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Air concentrations, especially from 1990 to 2010, were highest for those engaged in removal/replacement activities of RCF furnace linings, and in 2002, respiratory protection was required for these activities (Maxim & Utell, 2018; National Toxicology Program [NTP], 2016). A recent study of Chinese RCF workers ( n = 430) compared with controls ( n = 121) indicated that cumulative RCF and dust exposure levels in a non‐dose‐dependent manner were associated with altered levels of lung biomarkers (CC16 and TGF‐β1) and oxidative stress markers (8‐OHdG) (Gu et al, 2020). The International Agency for Research on Cancer (IARC) classified RCF as 2B, possibly carcinogenic to humans (IARC, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…associated with altered levels of lung biomarkers and oxidative stress markers (8-OHdG) (Gu et al, 2020). The International Agency for Research on Cancer (IARC) classified RCF as 2B, possibly carcinogenic to humans (IARC, 2002).…”
mentioning
confidence: 99%